Produção de periferias urbanas em cidades médias paulistas: o caso de São Carlos e São José do Rio Preto - Siqueira, Barbara Vallilo (Universidade Federal de São Carlos, 2015)
This paper aims at developing a better understanding of what has set up the new role of the medium-size cities in Sao Paulo in their urban network as well as how their forms of expansion have contributed to the continuity of the construction of cities increasingly unequal as regards the occupation of the territory. The addressed settings concern the production of Housing Projects of Social Interest promoted by the housing policy aimed at low-income families and the production of Closed Housing Projects associated with land and real estate interests. These modalities help in the spatialization of socio-territorial segregation and supports the understanding of the logic city center x outskirts. The research on two empirical objects aimed to illustrate how these settings appropriate the peripheral areas of the cities of Sao Carlos and Sao Jose do Rio Preto. In order to strengthen the argument, the application of three analyzing variables guided the reading of the processes that have been reinforced as well as the processes that have been provoked in the intra-urban scale. Although the origin of the phenomena is the result of disputes over the occupation of urban space, the analytical approach indicated the similarities and peculiarities which were found in each city.
Keywords: Medium-size Cities in Sao Paulo; Urban Peripheries; Socio-territorial Segregation; Cidades Médias Paulistas; Periferias Urbanas; Segregação Socioespacial; ENGENHARIAS